2020
DOI: 10.1038/s41467-020-18030-6
|View full text |Cite
|
Sign up to set email alerts
|

Probing consequences of anion-dictated electrochemistry on the electrode/monolayer/electrolyte interfacial properties

Abstract: Altering electrochemical interfaces by using electrolyte effects or so-called “electrolyte engineering” provides a versatile means to modulate the electrochemical response. However, the long-standing challenge is going “beyond cyclic voltammetry” where electrolyte effects are interrogated from the standpoint of the interfacial properties of the electrode/electrolyte interface. Here, we employ ferrocene-terminated self-assembled monolayers as a molecular probe and investigate how the anion-dictated electrochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 70 publications
(95 reference statements)
4
57
0
Order By: Relevance
“…This favorable adsorption could be attributed to the hydrophobic nature of the surfactant molecules and a pairing-induced charged group stabilization. [4,25] The ionovoltaic generation can be influenced by several factors such as the droplet motion-dependent contact area variation, resistor-capacitor discharging, and an interfacial potential difference between the electrolyte (droplet) and the Si electrode (∑ψ). [17,20] Among those factors, the first two terms had negligible effects to the output voltages changes (experimental section, Figure S6b, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This favorable adsorption could be attributed to the hydrophobic nature of the surfactant molecules and a pairing-induced charged group stabilization. [4,25] The ionovoltaic generation can be influenced by several factors such as the droplet motion-dependent contact area variation, resistor-capacitor discharging, and an interfacial potential difference between the electrolyte (droplet) and the Si electrode (∑ψ). [17,20] Among those factors, the first two terms had negligible effects to the output voltages changes (experimental section, Figure S6b, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that, with a rational design of interfacial molecular layer, the ionovoltaic system could be an analytic system for observing the ionic and intermolecular interactions, such as interfacial ad-/desorption and chemical reaction, at the interfacial region without intricate experimental conditions. In conjunction with conventional surficial and interfacial analytic techniques, such as optical measurements (e.g., IR and Raman scattering spectroscopy, sum frequency generation), [4,35,36] the ionovoltaic system might be an informative tool for analyzing solid/liquid interfacial phenomena in various liquid interfacing devices. [4,6,10]…”
Section: Supporting Informationmentioning
confidence: 99%
See 3 more Smart Citations